Challenges and Future Opportunities of Groundwater Resources for Drinking Water Use: A Case Study of Slatina nad Bebravou (Slovakia) - Marek Illes; Peter Lukac; Peter Halaj; Andrej Valek; Vera Hubacikova; Tatiana Kaletova (Hydrology)
The interlinked issues of climate change and increasing water demand are creating high pressure on water resources. In Slovakia, groundwater is a principal resource for human consumption. Consequently, an analysis was conducted of the current water yields of three springs, river discharges and precipitation trends, from several points of view. As a case study, we selected the area around Slatina nad Bebravou (Slovakia), which has the most relevant database. Descriptive statistics, the Mann–Kendall test and Sen’s slope were used for the trend analysis. The findings indicate that the current capacity of springs is sufficient to meet the present needs of water users. However, the downward trend in abundance, the increasing trend in water withdrawal, and the current poor state of infrastructure point to an early tipping point. Data analysis revealed a problem with the yield of springs, especially in the summer and autumn months.